Efficacy of Comforting Manoeuvres in Reducing Anxiety in Patients Undergoing Caesarean Section under Regional Anaesthesia- Randomised Control Trial - Pritam Yadav; Deepika Budhwar; Vineet Kumar; Suresh Singhal; Prashant Kumar; Rahul Saini (Journal of Clinical and Diagnostic Research, 2023)
Introduction: Comforting manoeuvres like hand holding and calming conversation with the parturients may decrease anxiety among them by establishing a rapport and building confidence and trust to alleviate fear. Aim: Evaluation of role and effectiveness of comforting manoeuvres (hand holding and calming conversation) in relieving patient’s anxiety and subjective satisfaction undergoing caesarean section in regional anaesthesia. Materials and Methods: This was a single centre randomised control trial conducted in the Department of Anaesthesiology and Critical Care, Post Graduate Institute of Medical Sciences, Rohtak, Haryana, India, from February 2022 to June 2022. There were 144 parturients, in the age group 18-40 years, American Society of Anaesthesiology (ASA) II, and admitted for Caesarean section under regional anaesthesia. Patients were randomised into four groups- control group (C)- group 1, only calming conversation (CC)- group 2, only Hand Holding (HH)- group 3 and Hand Holding and Calming Conversation (CH)- group 4. Demographic details of the patient, Visual Analogue Scale (VAS) for anxiety, Blood Pressure (BP), Heart Rate (HR), Respiratory Rate (RR) and patient satisfaction score on a 1-5 Likert scale were noted preoperatively. VAS was noted preoperatively and postoperatively for all groups. Patient Satisfication Score (PSS) was noted postoperatively. The HR, Mean Arterial Pressure (MAP), and RR were noted every 5 minutes for 20 minutes, then every 10 minutes till the end of the surgery, and 30 minutes after surgery. Any anxiolytic medication used intraoperatively was documented for all groups. Results: Total of 144 participants were analysed with 36 patients in each of four groups. Mean age (years) for group 1 was 23.36, group 2 was 23.25, group 3 was 23.17, and group 4 was 23.22. Baseline VAS was similar in all the groups. Post-operative VAS differed significantly - group 1 was 3.33±0.926, group 2 was 1.53±0.845, group 3 was1.47±0.845 and group 4 was 1.11±0.708. PSS also differed significantly - for group 1 was 2.42±0.732, group 2 was 3.50±0.697, group 3 was 3.67±0.717 and group 4 was 3.92±0.692. Stabilisation of hemodynamics in terms of BP, HR and RR was significantly better in all three interventional groups as compared to the control group. Conclusion: All three manoeuvres (hand holding, calming conversation alone and in combination) were equally effective in reducing perioperative anxiety, stabilising the hemodynamics and improving patient satisfaction in parturients undergoing caesarean section under regional anaesthesia. Comforting manoeuvres are simple, easy to practice and without any financial implication.